E-Module Research Trends in Learning Physics: Bibliometric Studies in 2017-2021 Range (Before and During the COVID-19 Pandemic) - Zainuddin Zainuddin; Surya Haryandi; Misbah Misbah; Winda Febriani; Siti Aisyah; Nida Supiati; Mohd Ali Ibrahim (IJORER : International Journal of Recent Educational Research, 2022)
The COVID-19 pandemic that has hit the world for the past two years has created a new trend in the world of education, one of which is through the use of e-modules. The purpose of this research is to identify and describe trends in e-module research in physics learning. The method used in this research is through bibliometric studies. The research was conducted by searching online through the Scopus database in July 2022 with the keyword "e-module" in the 2017-2021 range. The search results are then sorted and saved in CSV format which is then analyzed using VOSviewer software. Through this bibliometric approach, we can obtain an overview of research trends, patterns of interrelationships, and the potential to find novelty from these trends so as to assist further research in the future. The results of data analysis show that there are countries and the most productive authors who conduct research on e-modules. In addition, bibliometric visualization shows that research on e-modules continues to grow in various topics. So that research on e-modules in the future continues to develop according to needs.